2022
DOI: 10.3390/land11060891
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Ecological Migration on Land Use and Vegetation Restoration in Arid Zones

Abstract: Poverty and disasters are globally prevalent in ecologically fragile areas. Ecological migration is regarded as an effective way to address these issues. This paper investigates the spatial pattern of ecological migration and the corresponding spatiotemporal changes in land use and vegetation restoration in Gulang County, located in northwest China, between 2010 and 2018. For this purpose, we calculated three indicators: the transfer matrix of land use, normalized difference vegetation index (NDVI), and vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
2
7
1
Order By: Relevance
“…Furthermore, the RD and SY in the NVR were 84.2% and 99.9% lower than in the BL, respectively. This result suggested that revegetation resulted in less soil erosion, demonstrating the negative effects of converting natural grassland to cropland, which was confirmed by many studies (e.g., Xia et al, 2014; Yan, Zhen, et al, 2021; Zhang et al, 2022). These results showed that the conversion of natural grassland/forest to farmland reduced soil quality and increased soil erodibility because of more frequent soil disturbances and less vegetation coverage, plant community diversity and root density (Manzoni & Porporato, 2009; Mohammad & Adam, 2010; Vityakon, 2007).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, the RD and SY in the NVR were 84.2% and 99.9% lower than in the BL, respectively. This result suggested that revegetation resulted in less soil erosion, demonstrating the negative effects of converting natural grassland to cropland, which was confirmed by many studies (e.g., Xia et al, 2014; Yan, Zhen, et al, 2021; Zhang et al, 2022). These results showed that the conversion of natural grassland/forest to farmland reduced soil quality and increased soil erodibility because of more frequent soil disturbances and less vegetation coverage, plant community diversity and root density (Manzoni & Porporato, 2009; Mohammad & Adam, 2010; Vityakon, 2007).…”
Section: Discussionsupporting
confidence: 64%
“…The results presented in Tables 3 and 4 indicate that LULC classification of the three states has a great significant alignment with ground observation of the various land cover classes. Changes in land use are a direct indication of ecological migration [38]. As seen in Table 5, Figure 2a,b and Appendix A, in Niger state between 1990 and 2020, the agricultural land experienced the largest increase with an annual rate of 7.44 units, while barren land and vegetation had the largest decrease of above 7 units each per year.…”
Section: Accuracy Assessment Of Lulc Classificationmentioning
confidence: 98%
“…At the same time, the high mountains and steep slopes hinder the development of production and life. Therefore, the quality of the humanistic environment is the lowest, which also highlights the necessity and urgency of implementing immigration (Zhang W et al, 2022). In addition, there are many towns and larger villages scattered along the main transportation roads.…”
Section: Single Factor Suitability Of the Natural Environmentmentioning
confidence: 99%
“…The research data is transformed from survey data such as statistical yearbooks and questionnaire interviews into geographical data such as satellite images and land use (Wang et al, 2019); its evaluation index system covers physical geography, social economy, and public services. The research scale covers provinces (Yingying et al, 2022;, cities (Chen et al, 2022), villages (Zhao et al, 2019), communities (Aghamohammadi et al, 2021), and resettlement in arid areas (Gong et al, 2021;Zhang W et al, 2022).…”
Section: Introductionmentioning
confidence: 99%